2015
DOI: 10.1016/j.joca.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis-related biomarkers following anterior cruciate ligament injury and reconstruction: a systematic review

Abstract: Patients with ACL-D or ACL-R have altered biomarkers indicative of OA. More research with standardized reporting is needed to effectively determine which biomarkers are the most indicative for OA development and progression following ACL injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 44 publications
2
85
0
6
Order By: Relevance
“…This observation suggests that other factors such as altered biology 52; 53 , in addition to altered biomechanics, play a significant role in development of premature knee OA in the ACLR limb. It is also of interest to note that patient-reported outcome measures (Table 1) showed minimal changes from 2 to 8 years prospectively while gait demonstrated significant changes.…”
Section: Discussionmentioning
confidence: 97%
“…This observation suggests that other factors such as altered biology 52; 53 , in addition to altered biomechanics, play a significant role in development of premature knee OA in the ACLR limb. It is also of interest to note that patient-reported outcome measures (Table 1) showed minimal changes from 2 to 8 years prospectively while gait demonstrated significant changes.…”
Section: Discussionmentioning
confidence: 97%
“…None of these studies employ longitudinal sampling of SF from the same patients. A recent review of cross-sectional studies from ACL-injured patients [20] concluded that in the first week post-injury, [20] levels of IL-6, IL-8, and IL-1Ra were consistently elevated, while there was more variability in reported levels of IL-1α and β. In the subacute period (1 week to 2 months), IL-6 levels remain elevated across studies, and other cytokines and chemokines such as MCP-1, MIP-1β, and IFNγ have been reported.…”
Section: Methodsmentioning
confidence: 99%
“…49 In fact, up to 90% of ACL injuries are accompanied by osteochondral lesions, suggesting that trauma to the articular cartilage occurs with ACL rupture. 4 Increased presence of inflammatory markers and biomarkers of cartilage degradation have also been reported after ACL injury and reconstruction 50 and meniscal injury. 51 However, the prognostic importance of these biomarkers is presently unknown, as it is unclear if the elevated concentrations of these markers are a healthy or pathologic adaptation to injury.…”
Section: Risk Factors For Ptoa Joint Injurymentioning
confidence: 98%
“…51 However, the prognostic importance of these biomarkers is presently unknown, as it is unclear if the elevated concentrations of these markers are a healthy or pathologic adaptation to injury. 50 Altered loading about the injured joint has also been suggested to contribute to PTOA development. Biomechanical changes in ACL-deficient and -reconstructed individuals may change the regions where tibiofemoral joint contact occurs, thereby loading areas of cartilage that were previously unloaded and decreasing loads to areas of cartilage normally experiencing higher loads during weight bearing.…”
Section: Risk Factors For Ptoa Joint Injurymentioning
confidence: 99%